This is an integral I computed but can't find the result online or on wolfram. So here's a proof sketch, please indulge this sanity check:

$$\int_0^\infty x \left \lfloor{\frac1x}\right \rfloor \ dx = \int_0^1 x \left \lfloor{\frac1x}\right \rfloor \ dx$$ $$= \sum_{n=1}^\infty \int_{1/(n+1)}^{1/n} nx \ dx =\sum_{n=1}^\infty\frac n2 \left(\frac{1}{n^2} - \frac{1}{(n+1)^2}\right) $$ $$= \sum_{n=1}^\infty\frac n2 \left(\frac{2n+1}{n^2(n+1)^2}\right)$$ $$= \sum_{n=1}^\infty\frac{1}{(n+1)^2} + \frac12 \sum_{n=1}^\infty \frac{1}{n(n+1)^2}$$ $$= \frac{\pi^2}{6} -1 + \frac12\left(\sum_{n=1}^\infty \frac1n - \frac{1}{n+1} - \frac{1}{(n+1)^2}\right)$$ $$=\frac{\pi^2}{6} -1 + \frac12\left(\sum_{n=1}^\infty \frac1n - \frac{1}{n+1}\right) -\frac12\left(\sum_{n=1}^\infty\frac{1}{(n+1)^2}\right)$$ $$= \left(\frac{\pi^2}{6} -1\right) + \left(\frac12\cdot 1\right) - \frac12\left(\frac{\pi^2}{6} -1\right)$$ $$= \frac{\pi^2}{12}.$$

Basically, I used the Basel sum several times, and the fifth line follows from a partial sum decomposition. The seventh follows from the known result for the Basel sum, as well as the fact that the first series in the 6th line telescopes.

I hope this is all correct.

  • $\begingroup$ @XanderHenderson For $x>1$, floor of $\frac{1}{x}$ is $0$ $\endgroup$ – BallBoy Dec 28 '17 at 3:34
  • $\begingroup$ @XanderHenderson What you wrote is certainly not true, because you forgot the $x$ term. However, what Y. Forman says is correct, and I should've been more explicit there. $\endgroup$ – David Bowman Dec 28 '17 at 3:37
  • 1
    $\begingroup$ Oi... derp. Sorry for being dyslexic. I missed the $x$. $\endgroup$ – Xander Henderson Dec 28 '17 at 3:39
  • 15
    $\begingroup$ $$\int_0^1 x \lfloor 1/x \rfloor dx = \int_1^\infty \frac{1}{t} \lfloor t \rfloor \frac{dt}{t^2}= \sum_{n=1}^\infty \int_n^\infty t^{-3}dt = \sum_{n=1}^\infty \frac{n^{-2}}{2} = \frac{\zeta(2)}{2}$$ $\endgroup$ – reuns Dec 28 '17 at 3:43
  • 1
    $\begingroup$ @reuns Nice, better post it as answer! $\endgroup$ – samjoe Dec 28 '17 at 4:40


$$n\left(\frac1{n^2}-\frac1{(n+1)^2}\right)=\frac n{n^2}-\frac{n+1-1}{(n+1)^2}=\frac1n-\frac1{n+1}+\frac1{(n+1)^2}.$$

The first two terms do telescope and the Basel series remains.

  • $\begingroup$ @stressedout: of course, but much simpler. And also simpler than yours, which is also essentially the OP's. $\endgroup$ – Yves Daoust Sep 5 '18 at 6:28
  • $\begingroup$ @stressedout: your solution isn't different, just longer. A one-liner is simpler. $\endgroup$ – Yves Daoust Sep 5 '18 at 6:38

Alternatively, one may follow the same line of thought and use summation by parts formula to calculate the infinite sum. Similarly, $$\int_0^{+\infty} x\lfloor \frac{1}{x}\rfloor dx =\sum_{n=1}^{\infty}\frac{n}{2}\left(\frac{1}{n^2}-\frac{1}{(n+1)^2}\right)=-\frac{1}{2}\sum_{n=1}^{\infty}f_n(g_{n+1}-g_n)$$

where $f_n = n$ and $g_n = 1/n^2$. Now, summation by parts for the last expression gives:

$$-\frac{1}{2}\sum_{n=1}^{\infty}f_n(g_{n+1}-g_n) = -\frac{1}{2}\left(\ \lim_{n\to\infty}\frac{n}{(n+1)^2} -1 -\sum_{n=2}^{\infty}\frac{1}{n^2}\right)$$

But it is well-known that $$\sum_{n=1}^{\infty}\frac{1}{n^2}=\frac{\pi^2}{6}$$


$$-\frac{1}{2}\sum_{n=1}^{\infty}f_n(g_{n+1}-g_n) = -\frac{1}{2}\left(\ \lim_{n\to\infty}\frac{n}{(n+1)^2} -1 - (\frac{\pi^2}{6}-1)\right) = \frac{\pi^2}{12}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.